Communication—Luminescence Properties of a Novel l Rb2KGaF6:Mn4+ Red-Emitting Phosphor for Solid-State Lighting. (16th November 2020) - Shi, Dongxin; Xie, Xiaoling; Pu, Haiqi; Zhang, Xi; Zhou, Qiang; Wang, Zhengliang; Ye, Yanqing; Chen, Minghong
Abstract : A novel red-emitting Rb2 KGaF6 :Mn 4+ phosphor with octahedral particulate morphology was presented. The XRD Rietveld refinement results indicate that the phosphor crystallized into the cubic phase of Fm 3 ̄ m space group with double perovskite structure. The photo-luminescence spectrum exhibits intense red emission lines with zero-phonon line (ZPL) and v 6 peak locating at 620 and 628 nm respectively. The optical parameters of low color temperature ( T c = 3824 K) and high color rendering index ( R a = 90.2 ) from white LED imply its potential application in solid-state lighting.